MEDIA AND SOCIAL CONSTRUCTION BASED ON LOCAL WISDOM IN COVID 19 DISASTER MANAGEMENT IN SUMENEP DISTRICT - Zuhdi, Moh; Ikmal, Moh (JURNAL SETIA PANCASILA, 2022)
The purpose of this study was to find out how social and media construction was built as part of the early Covid-19 mitigation efforts by the Sumenep district government and how the institutional role of volunteer groups in efforts to cope with the Covid-19 disaster in Sumenep district. This research is a qualitative-descriptive research by taking the research subject of person and paper. The subjects of the paper are written documents in the form of legislation or other library materials that have relevance to the research data, while the subject persons are stakeholders and community groups at the research location (Batang-Batang and Bluto). The results of this study indicate that the handling of the Covid 19 disaster in Sumenep Regency was carried out with several steps including 1) strengthening community involvement through coordination meetings with village heads, community leaders and leaders of religious organizations, 2) stimulus policies in the form of giving gifts to the community (sembako, and door prizes). , 3) involvement of ulama figures through moral testimony, 4) pick-up technique for villagers